Rhetorik : Ein internationales Jahrbuch (De Gruyter, 1980)
As a persuasive technique, a subject of school instruction, and a social practice, rhetoric has shaped our literary, linguistic, and social lives since the fifth century BC. Today, it plays a major role in sales, management, and advertising. This yearbook gathers research on rhetoric in Germany, and also features an extensive review section highlighting the latest publications in the field.